Sistem Pendukung Keputusan Dalam Penentuan Promosi Jabatan Menggunakan Metode AHP dan SMART - Resanda Dianggara Widoproyo; Putri Aisyiyah Rakhma Devi (Universitas Budi Darma, 2022)
Company competition to be the best in the current era of globalization is getting tighter. Employees at the company are one of the keys for companies to be able to compete by increasing their abilities and placing the right positions in accordance with the skills possessed by these employees. Position promotion can be done if it is done effectively and efficiently. The same is the case at PT.Fokus Jasa Mitra which carries out promotions to employees who will occupy new positions. However, the determination process is still less effective and efficient because the calculation process is still manual. Therefore, a decision support system is needed to solve the existing problems, the authors use a combination of the AHP (Analytical Hierarchy Process) and SMART (Simple Multi Attribute Rating Technique) methods which can produce a weighting for each criterion and the final value of the alternative that is ranked first. In this study, the results of the calculations obtained, the best value or being the first rank of the twenty alternative data is Alternative 2 with a final value of 61,784 so that this calculation can be said to be effective and efficient.